2009
DOI: 10.1021/cg800992f
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism, Composition, and Structural Variability in Topology in 1D, 2D, and 3D Copper Phosphonocarboxylate Materials

Abstract: ABSTRACT:The syntheses and structural characterization of 1D, 2D, and 3D materials based on copper phosphonocarboxylate backbones are described. More specifically, the synthesis of materials from diethylphosphonoacetic acid (DEPAA) or the close variant hydroxyphosphonoacetic acid (HPAA) and water-soluble Cu 2+ salts has been studied. The initial synthesis involving copper acetate and DEPAA was carried out at 160°C under hydrothermal conditions and a Cu:P ratio of 1:1 resulted in the formation of a mixture of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 52 publications
0
27
0
Order By: Relevance
“…In contrast, high pH values cause deprotonation, high negative charge on the phosphonate and rapid formation and precipitation of an amorphous metal phosphonate product. Hence, for each metal/phosphonate system there is an optimum pH regime for crystalline product formation [49].…”
Section: Synthetic Considerationsmentioning
confidence: 99%
“…In contrast, high pH values cause deprotonation, high negative charge on the phosphonate and rapid formation and precipitation of an amorphous metal phosphonate product. Hence, for each metal/phosphonate system there is an optimum pH regime for crystalline product formation [49].…”
Section: Synthetic Considerationsmentioning
confidence: 99%
“…The phosphonate oxygen atom O(3) is not involved in any hydrogen bond. Lodhia et al [24] reported on a triclinic copper hydrogenphosphonoacetate monohydrate in which each hydrogenphosphonoacetate dianion is coordinated to three Cu 2+ cations.…”
Section: Cu[µ2-ooc(ch2)po3h]⋅2h2o (1)mentioning
confidence: 99%
“…The connection between Cu 2+ and phosphonoacetate anions leads to coordination polymers with one-, two and three-dimensional structural features. [19,23,24] The obtained structures depend on the reaction temperature, Cu:P ratio, pH value, and the deprotonation stage of the phosphonoacetate anion. The structures of Cu(II) phosphonoacetates can be modified using additional N-donor ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[Cu 4 (O 3 PCH 2 CO 2 ) 2 (5-dmbpy) 4 Table S1 and Figure S4) and involving the terminal aqua ligand, the perchlorate ion, and the phosphonate moieties form a supramolecular 1D system extended along the c axis of the triclinic unit cell in 5 (Supporting information, Table S1 and Figure S5). …”
Section: [Cu 2 (Ho 3 Pch 2 Co 2 ) 2 (Bpy) 2 ] (3)mentioning
confidence: 99%